Protective Effect of Aqueous Extract of Rhuscoriaria L. Fruit on Catalase Enzyme Activity and Histopathology of Liver in Alloxan-Induced Diabetic Rats - Z Salimi (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2012)
Background and Objectives: Complications in diabetes mellitus are associated with free radicals and oxidative stress. The human body copes with these complications through antioxidant defense mechanisms. This study aimes at assessing the effect of aqueous extract of sumac (Rhus coriaria L.) fruit on catalase (CAT) enzyme activity and the histopathological changes of liver in diabetic rats. Methods: In this study, 30 adult male Wistar rats, with average weight 180-230g were divided randomly into 5 groups of 6 rats. Physiological serum was injected to control rat group with the same volume of injection material. The second group of rats, became intraperitonally diabetic by injecting 120mg/kgbw dose of Alloxan monohydrate. The third, fourth and fifth groups of rats in addition to the same treatment of the second group, were fed aqueous extract of Rhus coriaria respectively, 50, 100 and 250mg/kgbw doses for 4 weeks. At the end of treatment, the role of extract on CAT enzyme activity was assessed. The serial sections of liver were prepared and stained with H & E for microscopic investigations. Data were analyzed using the test one way ANOVA and Tukey test. Significant level (p<0.05) was considered. Results: CAT enzyme activity decreased in diabetic group significantly (p<0.05). Moreover, CAT enzyme activity in group treated with extract (250mg/kgbw) was significantly different as compared to diabetic group (p<0.05). Also those treated with extract, (250mg/kgbw) indicated a significant improve in side-effects of diabetes mellitus on liver tissue in diabetic rats. Conclusion: These results show that Sumac can be effective in decreasing diabetic complications and it can be used as an antioxidant and food supplement in diabetic patients.